1988
DOI: 10.1093/ajcn/48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of nutrition knowledge and attitudes of medical students at three points in their medical training at 11 southeastern medical schools

Abstract: Eleven southeastern medical schools cooperated to evaluate nutrition knowledge and attitudes of medical students. This study complements previous reports of an examination of entering freshmen and seniors. Average knowledge scores for 165 students tested after basic sciences (preclinical) training in this study were 67 +/- 7% compared with 53 +/- 6% for freshmen and 69 +/- 8% for seniors. The upperclassmen's scores were higher than the freshmen's (p less than 0.001) and varied with the amount of required nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…Prior exposure to nutrition was presumably minimal [19]. And while multiple studies of the immediate impact of nutrition interventions among medical students found improvements in knowledge, confidence, and self efficacy [20,21], our work, similar to others [22], suggests there may be a deterioration of these gains and raises questions about the optimal timing of nutrition education and its' integration into the medical education curriculum.…”
Section: Discussionsupporting
confidence: 61%
“…Prior exposure to nutrition was presumably minimal [19]. And while multiple studies of the immediate impact of nutrition interventions among medical students found improvements in knowledge, confidence, and self efficacy [20,21], our work, similar to others [22], suggests there may be a deterioration of these gains and raises questions about the optimal timing of nutrition education and its' integration into the medical education curriculum.…”
Section: Discussionsupporting
confidence: 61%
“…The results of the final‐year students’ attitude towards nutrition in the present study are consistent with previous studies, which reported that nutrition care is perceived to be important by medical students 19,42–44 . Previous research has reported that the positive attitude of new medical students toward nutrition is lost after preclinical training and is only partially regained after the clinical years 45 . The fading interest of medical students can be explained by a lack of role models teaching about incorporating nutrition care into medical practice 46 …”
Section: Discussionsupporting
confidence: 91%
“…In a study of students from 11 medical schools, 74% of newly arrived medical students believed that nutrition would be important for their careers, but only 59% held that view by the end of medical school. 11…”
Section: Nutrition Education In Medical Schoolmentioning
confidence: 99%